Studies in symbolic interaction. Vol. 31 - Salvo, James; Washington, Myra. (Bingley : JAI, 2008)
This new volume provides a theoretical and empirical perspective on the value, potential and contribution that qualitative research methodologies bring to the analysis of housing policy issues within an international context. This encompasses key housing issues, including: the meaning and significance of home; homelessness; resident participation; housing renewal and gentrification; socially mixed housing communities; Irish Gypsies; and post-apartheid housing policies. The book also includes discussion of specific methodological challenges and ethical dilemmas faced by researchers (and policy-makers). The book's core strength lies in its ability to showcase the versatility and practical application of qualitative research in housing studies.
Includes "Blue-Ribbon papers series."
Includes bibliographical references.
Description based on print version record.
Keywords: Symbolic interactionism; Social interaction; Interpersonal communication; Social welfare & social services; Social Science -- Research; Social Science -- Sociology -- General